2005
DOI: 10.7202/010907ar
|View full text |Cite
|
Sign up to set email alerts
|

Effect of five postemergence herbicides on red clover shoot and root growth in greenhouse studies

Abstract: Société de protection des plantes du Québec (SPPQ)ISSN 0031-9511 (imprimé) 1710-1603 (numérique) Découvrir la revue Citer cet article Ceballos, R., Palma, G., Brevis, H., Ortega, F. & Quiroz, A. (2004). Effect of five postemergence herbicides on red clover shoot and root growth in greenhouse studies. Phytoprotection, 85(3), 153-160. doi:10.7202 MCPA, 2,4-DB, flumetsulam, bentazon, haloxyfop-methyl, flumetsulam/2,4-DB and bentazon/MCPA were studied in greenhouse experiments in order to evaluate their prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 23 publications
2
16
0
3
Order By: Relevance
“…The phytotoxic effect of MCPA, bentazon, 2,4-DB, flumetsulam, haloxifop-methyl, and of the mixtures usually used on red clover as flumetsulam/2,4-DB and bentazon/MCPA herbicides have been reported (Ceballos et al, 2004). In our study, all the herbicides were evaluated at recommended and twice recommended rate and all caused early foliar damage, but bentazon and bentazon/MCPA produced the greatest shoot damage.…”
Section: Introductionmentioning
confidence: 52%
See 3 more Smart Citations
“…The phytotoxic effect of MCPA, bentazon, 2,4-DB, flumetsulam, haloxifop-methyl, and of the mixtures usually used on red clover as flumetsulam/2,4-DB and bentazon/MCPA herbicides have been reported (Ceballos et al, 2004). In our study, all the herbicides were evaluated at recommended and twice recommended rate and all caused early foliar damage, but bentazon and bentazon/MCPA produced the greatest shoot damage.…”
Section: Introductionmentioning
confidence: 52%
“…Fusarium root rot is a common disease in Chilean red clover pastures, as well as in other areas in the world (Ceballos et al, 2004(Ceballos et al, , 2006Galdames, 1991;Steiner and Alderman, 1999;Venuto et al, 1995), causing reductions in productivity and persistence (Coulman and Lambert, 1995;Leath, 1985;Venuto et al, 1996). Fusarium oxysporum Schldt.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ceballos et al (2004) detected 2,4-D root injury at the beginning of the experiment. Moreover, Garcia and Jordon (1969) found that nodulation and nitrogen fixation in birdsfoot trefoil (Lotus corniculatus L.) were reduced by 2,4-D. Martensson (1992) reported that, despite the ability of certain Rhizobium trifolii strains to detoxify glyphosate, its use inhibited root nodulation in red clover (Trifolium pratense).…”
Section: Treatmentsmentioning
confidence: 99%